1990
DOI: 10.1002/nur.4770130106
|View full text |Cite
|
Sign up to set email alerts
|

Temperament, Behavior Problems, and Learning Skills in Very Low Birth Weight Preschoolers

Abstract: The relationship between temperament, behavior problems, and learning skill abilities in preschool children who were born with very low birth weight (VLBW) is described. Subjects were 37 4-year-olds who weighed less than 1,500 grams at birth, were appropriate for gestational age, and free from congenital anomalies (M birth weight = 1,201 grams). Data were gathered when the children were 48 months chronological age and analyzed using point biserial and Pearson product moment correlation, chi square, and MANOVA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Vohr, Garcia-Coll, and Oh (1989) found attention problems in 31% of their sample of low-birthweight infants when seen at 3 years of age. Maternal reports in one study of 4-year-old low-birthweight preschoolers identified 67% with behavior problems and 37% with attention problems (Schraeder, Heverly, & Rappaport, 1990).…”
Section: Attention and Behavior Problemsmentioning
confidence: 99%
“…Vohr, Garcia-Coll, and Oh (1989) found attention problems in 31% of their sample of low-birthweight infants when seen at 3 years of age. Maternal reports in one study of 4-year-old low-birthweight preschoolers identified 67% with behavior problems and 37% with attention problems (Schraeder, Heverly, & Rappaport, 1990).…”
Section: Attention and Behavior Problemsmentioning
confidence: 99%
“…Other researchers have also reported similar ndings, in particular, when children with possible mental impairment at birth were excluded from the studied group. Furthermore, other investigators have emphasised a greater incidence of learning problems (Als, 1985;Calame et al, 1986;Schraeder, Heverley, & Rappaport, 1990) or even variations in temperament (Schraeder & Tobey, 1989;Spungen & Farren, 1986): Low birthweight children had greater dif culties with respect to rhythm, persistence and mood than children born at term as healthy, normal birthweight infants.…”
Section: Long-term Morbiditymentioning
confidence: 99%
“…Over the past two decades researchers have studied numerous biological and environmental factors thought to influence the development of childhood behavior problems with varying results. Biological factors, such as preterm birth, pose a significant risk for the development of behavior problems (Greenberg, Carmichael-Olson, & Cmic, 1992;Schraeder, Heverly, & Rappaport, 1990). Preterm infants have been shown to be less alert, less active, and less responsive in their interactions during their first few months than full term infants, even though mothers are more active and stimulating in interactions with their preterm infants (Barnard, Bee, & Hammond, 1984).…”
mentioning
confidence: 99%